TINGKAT PENGGUNAAN SANTAN KELAPA DAN TEPUNG UBI HUTAN (Dioscorea hispida dennts) PADA PEMBUATAN ES KRIM - Anwar M. Koyo; Umbang Arif Rokhayati; Agus Bahar Rachman (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2016)
Ice cream is a frozen dairy products from a solid milk made from a mixture of milk. The nutrition of ice cream depends on nutrition of raw material that is used. This study aimed to examine the use of coconut milk and cassava forest flour in ice cream with 4 treatments (T0=0 g coconut milk and 0 g cassava forest flour; T1=25 g coconut milk and 75 g cassava forest flour; T2=50 g coconut milk and 50 g cassava forest flour; T3=75 g coconut milk and 25 g cassava forest flour) and 4 replications. Paratemeter used in this study is analysis of water and fat content, melting time and hedonic quality (aroma, texture and flavor). This study used Completely Random Design to analyze the result. Organoleptic test was analyzed by Analysis of Variance and melting time test was analyzed descriptively. The results showed that proximate analysis of water content with the highest value found in the treatment of 75 g coconut milk and 25 g cassava forest flour and the lowest was found in the treatment of 0 g coconut milk and 0 g cassava forest flour. The highest fat content found in the treatment of 75 g coconut milk and 25 g cassava forest flour and the lowest was found in the treatment of 0 g coconut milk and 0 g cassava forest flour. The results of organoleptic test showed that percentage of aroma treatment was T0=2,40, T1=2,45, T2=2,55, and T3=2,70. The percentage of texture of each treatment was T0=3,25, T1=3,25, T2=3,30, and T3=3,65. The percentage of flavour of each treatment was T0=3,55, T1=3,60, T2=3,65, and T3=3,75. The conslusion is that ice cream production by using coconut milk and cassava forest flour (Dioscorea hispida dennts) gave the significant effect to the water and fat content. It was also liked by panelist. Ice cream production by using 75 g coconut milk and 25 g cassava forest flour increased the melting time up to 19,44.